2011
DOI: 10.1128/aem.01901-10
|View full text |Cite
|
Sign up to set email alerts
|

Production of Secretory and Extracellular N-Linked Glycoproteins inEscherichia coli

Abstract: The Campylobacter jejuni pgl gene cluster encodes a complete N-linked protein glycosylation pathway that can be functionally transferred into Escherichia coli. In this system, we analyzed the interplay between N-linked glycosylation, membrane translocation and folding of acceptor proteins in bacteria. We developed a recombinant N-glycan acceptor peptide tag that permits N-linked glycosylation of diverse recombinant proteins expressed in the periplasm of glycosylation-competent E. coli cells. With this "glycosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 64 publications
(66 reference statements)
3
110
0
Order By: Relevance
“…The fact that Peb3 appears to be localized in the periplasm coupled with the reduction in the amount of Peb3 in pglB mutant OMVs compared to wild-type OMVs suggests that N-linked glycosylation may also play a role in OMV cargo selection. This is supported by the previous observation that when the C. jejuni N-linked glycosylation pathway is functionally transferred into E. coli, N-linked glycoproteins are identified within E. coli OMVs (20).…”
Section: Figsupporting
confidence: 79%
“…The fact that Peb3 appears to be localized in the periplasm coupled with the reduction in the amount of Peb3 in pglB mutant OMVs compared to wild-type OMVs suggests that N-linked glycosylation may also play a role in OMV cargo selection. This is supported by the previous observation that when the C. jejuni N-linked glycosylation pathway is functionally transferred into E. coli, N-linked glycoproteins are identified within E. coli OMVs (20).…”
Section: Figsupporting
confidence: 79%
“…It was also demonstrated that the transient presence of the protein in the periplasm was sufficient for glycosylation to occur and glycoproteins could subsequently be trafficked to the outer membrane or even to the extracellular environment. This novel finding will be crucial for the engineering of future acceptor proteins for PGCT, particularly in the biosynthesis of novel glycoconjugate vaccines (Fisher et al, 2011).…”
Section: Alternative Bacterial Glycosylation Systems For Use In Pgctmentioning
confidence: 90%
“…For example, exotoxin A from P. aeruginosa is not naturally recognized by CjPglB but following the addition of two sequons, the modified protein can accept glycans and is now being tested as a glycoconjugate vaccine (Ihssen et al, 2010). Initially, it was considered that care had to be taken when selecting the grafting site in order not to interfere with the structural stability of the protein; however, it has been recently demonstrated that tags containing the ideal consensus sequence (glycotags) can be added to the N-and C-termini of proteins (Fisher et al, 2011). This means that it is not …”
Section: Protein Glycan Coupling Technology (Pgct)mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make E. coli produce N-linked glycoproteins the gene cluster pgl, responsible for glycosylation in Campylobacter jejuni (Szymanski et al, 1999;Abu-Qarn et al, 2008) was successfully transferred (Wacker et al, 2002). Moreover, combination of the pgl system with a simple, genetically encoded glycosylation tag, expands the glycosylation possibilities of E. coli (Fisher et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%